The effects on prescribing patterns and costs of having a special interest in asthma. - Jones, K P (1995)
To define the characteristics of general practices with a special clinical interest in asthma and to estimate the resulting extra prescribing costs, we sent a postal questionnaire to all English practices containing members of the General Practitioners in Asthma Group. Item and cost comparisons for 24 PACT (prescribing analysis and cost) aggregates were made between practices who had operated an agreed, written management plan for asthma before 1 April 1990 and all other practices in their respective Family Health Services Authorities. One hundred and sixty-three practices with GPIAG members responded (70%), of which 26 filled the management plan requirement. These 26 practices showed evidence of significantly better asthma care provision than the remainder of the sample. Their prescribing costs were significantly higher for respiratory drugs (median 37% higher) but lower in other drug categories. For respiratory drugs, costs were significantly higher for inhaled adrenoceptor stimulants, steroid inhalers, large spacers, and peak flow meters, but lower for cough medicines and systemic nasal decongestants: the number of items prescribed showed similar patterns. The prescribing costs of practices claiming a special interest in asthma are likely to show higher respiratory drug costs, but overall prescribing costs showed no increase in the practices studied.